Andrea Bachner. The Mark of Theory: Inscriptive Figures, Poststructuralist Prehistories. Fordham UP, 2018. - Andrew Kettler (Studies in 20th & 21st Century Literature, 2019)
Review of Andrea Bachner. The Mark of Theory: Inscriptive Figures, Poststructuralist Prehistories. Fordham UP, 2018. 274 pp.
Keywords: inscription; theory; history